Association Between Glycemic Control (HbA1c) and Neutrophil to Lymphocyte Ratio in Patients with Type 2 Diabetes Mellitus at a Tertiary Hospital in Indonesia - Caecilia Ivana Alice Un Bria; Elisabeth Levina S. Setianingrum; Herman P. L. Wungouw; Teguh Dwi Nugroho (Jurnal Biologi Tropis, 2026)
Diabetes Mellitus Type 2 (DMT2) is a metabolic disorder that usually involves chronic inflammatory responses. The Neutrophil–Lymphocyte Ratio (NLR) is often utilized as a simple and cost-effective indicator of inflammation in the entire body. However, studies examining its connection to HbA1c, which indicates long-term glucose management, reveal inconsistent findings across various populations. This study aimed to assess the relationship between HbA1c levels and NLR values among T2DM patients attending the Internal Medicine Clinic of Mgr. Gabriel Manek Hospital, Atambua. This analytical observational study employed a cross-sectional design. The sample consisted of 62 outpatients with T2DM, selected through accidental sampling between August and November 2025. HbA1c levels and leukocyte differential counts used to calculate NLR were obtained from medical records. Data were analyzed using the Spearman Rank correlation test due to non-normal distribution. Most respondents were female (56.5%) and aged 46–55 years (51.6%). A large proportion of patients demonstrated suboptimal glycemic control (HbA1c ≥ 7%) at 91.9%. NLR values were predominantly within the normal range (79.0%). Statistical analysis showed no significant relationship between HbA1c levels and NLR (p = 0.321; r = 0.128). This study found no meaningful correlation between HbA1c levels and NLR among T2DM outpatients in the study setting. The findings suggest that in stable outpatient populations, elevated HbA1c levels may not directly reflect systemic inflammatory activity as measured by NLR.